Moderasi Beragama di Kawasan Pedesaan - Miftah, Zaini; Ni’mah, Roudlotun (Fakultas Agama Islam Universitas Billfath, 2023)
Religion plays an important role in social life to regulate human life and direct it to goodness in the world. This study aims to gain an understanding and description of religious moderation and religious harmony in rural areas, specifically the village of Legowetan. This study uses a phenomenological qualitative research method. Documentation, interviews, and observations are used as data collection techniques. This study resulted in: (1) Patterns of social interaction in Legowetan Village that are associative, such as adaptation, cooperation, and assimilation. (2) From the results of observations in the field, there are at least four indicators of the model of religious moderation carried out in the village of Legowetan, namely tolerance, non-violence, acceptance of tradition, and national commitment. These four models can be observed in the activities carried out by the Legowetan village community, namely religious activities, village activities, and artistic activities.